A Titan exits stage left: Summary of the Waun Ki Hong Festschrift. Issue 16 (6th May 2015) - Khuri, Fadlo R.
<x xml:space="preserve">Abstract</x> On August 15, 2014, at The University of Texas MD Anderson Cancer Center in Houston, Dr. Fadlo Khuri, along with co‐chairs Drs. James Abbruzzese, Patrick Hwu, Roy Herbst, and Scott Lippman, chaired a Festschrift celebrating the lifetime of accomplishments of Dr. Waun Ki Hong. A series of lectures celebrating Dr. Hong's legacy ensued, highlighting his accomplishments in the areas of induction chemotherapy, organ preservation, head and neck biology, carcinogenesis, and chemoprevention, as well as his leadership in the biological interrogation of biomarker‐driven pathways in lung and head and neck cancer and his transformation of the culture of mentorship and multidisciplinary science at The University of Texas MD Anderson Cancer Center.